Desain Kearifan Lokal Gorontalo sebagai Bahan Kajian dalam Pembelajaran Sains - Ihsan, Maimun; Lukum, Astin; Jusuf, Muhammad Isman (Jambura Journal of Educational Chemistry, 2024)
The development of science and technology has a spirit that does not necessarily need to be translated, indicating that science can be related to academic studies associated with physics, chemistry, biology, as well as other natural sciences such as geology and astronomy. Science also means looking closely at social, economic, psychological, humanities and even educational phenomena. Lokal wisdom which has the value of indigenous science is a traditional custom passed down from generation to generation in Indonesia which needs to be supported by educational experts to be researched so that it is hoped that it will become scientific science. In Gorontalo there are several studies regarding indigenous science becoming scientific knowledge, such as discussions about panggoba related to astronomy and agrotechnology; payango (in the field of house building engineering/architecture), yinthu tuluhe plant for the health sector (medicine for skin diseases). Other research has been carried out on the benefits of tubile (tuba roots) for fish poison (piscisida), mongubingo which has religious, cultural and health value. However, it is realized that the design of Gorontalo lokal wisdom as study material in science learning is still very poorly studied. Referring to these phenomena and real facts, it is deemed necessary to carry out research using the literature study method (library) with the topic "Gorontalo Lokal Wisdom Design as Study Material in Science Learning."